THE CORRELATION BETWEEN MULTIPLE INTELLIGENCES AND LANGUAGE LEARNING STRATEGIES OF THE ELEVENTH-GRADE STUDENTS AT RIAU VOCATIONAL HIGH SCHOOL FOR INTEGRATED AGRICULTURE - Robi Kurniawan; Aji Wijaya (XXXXXXXX, 2022)
This research aimed to investigate the preferred Multiple Intelligences (MI) and Language Learning Strategies (LLS) used by the eleventh-grade students of Integrated Agriculture Vocational High School. In addition, the researcher also looked for any relationships of each Multiple Intelligence profiles and different use of Language Learning Strategies. The multiple Intelligences questionnaire by Armstrong (2009) was used to identify the dominant intelligence among the students. While Students Inventory Language Learning Strategies (SILL) by Oxford (1990) was administered to know the students’ used learning strategies. Fifty-five (55) eleventh-grade students were chosen randomly to participate in this study. The result of the descriptive and inferential analysis showed that all of the students could excel in all types of intelligence at high and medium levels, then language learning strategies were mostly used at high and medium levels and rarely used at a low level. While Pearson Product Moment Correlation analysis revealed that each type of multiple intelligence and language learning strategy was having a significant correlation, as well as Linguistic, Logical, and Musical intelligence, which had medium and low correlations to all types of strategies except social strategy. Similarly, Visual intelligence had a medium and low correlation to all different uses of strategy. Yet, Kinesthetic intelligence only correlated to Memory and Compensation Strategy.  Keywords: multiple intelligences, language learning strategies